Freud, psychoanalysis, and symbolism - Petocz, Agnes (Cambridge University Press, 1999)
"Freud, Psychoanalysis and Symbolism offers an innovative general theory of symbolism, derived from Freud's psychoanalytic theory and relocated within mainstream scientific psychology. Agnes Petocz argues that the treatment of symbolism must begin with the identification and clarification of a set of logical constraints and psychological requirements which any general theory of symbolism must respect, and that these requirements have been neglected by existing accounts across a number of disciplines. Her newly proposed 'Freudian Broad' theory of symbolism, by contrast, does meet these requirements, but only after it has been rehabilitated within a revised psychoanalytic context."--Jacket